Generation of a safe and efficacious llama single-domain antibody fragment (vHH) targeting the membrane-proximal region of 4-1BB for engineering therapeutic bispecific antibodies for cancer. Issue 6 (25th June 2021) - Zhai, Tianhang; Wang, Chao; Xu, Yifeng; Huang, Weifeng; Yuan, Zhijun; Wang, Tao; Dai, Shuang; Peng, Shaogang; Pang, Tuling; Jiang, Wenchao; Huang, Yuhua; Zou, Yuefeng; et al.
Abstract : Background: The discovery of checkpoint inhibitors towards cytotoxic T-lymphocyte protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) has been revolutionary for the treatment of cancers. These therapies have only offered an average of 20%–30% response rates across the tumor spectrum and the combination of agonists towards the tumor-necrosis superfamily members, such as 4-1BB and CD40, has shown potent efficacy in preclinical studies; however, these agonists have exhibited high degrees of toxicity with limited efficacy in human trials. In this study, we have generated a single-domain antibody towards a unique epitope of 4-1BB that limits its potential on-target toxicity while maintaining sufficient potency. This 4-1BB binder is ideal for use in the engineering of multispecific antibodies to localize 4-1BB activation within the tumor microenvironment, as shown here by a anti-PD-L1/4-1BB bispecific candidate (PM1003). Methods: To determine the functional activity of the 4-1BB- and PD-L1-binding elements of PM1003, in vitro luciferase reporter and primary cell assays were used to test the potency of programmed cell death 1 ligand 1 (PD-L1) blockade and PD-L1-mediated 4-1BB activation via cross-bridging. X-ray crystallography was conducted to resolve the binding epitopes of the respective binding arms, and accurate binding kinetics were determined using standard affinity measurement techniques. Human 4-1BB and/or PD-L1 knock-in mice were used in cancer models for testing the in vivo antitumor efficacy of PM1003, and safety was evaluated further. Results: PM1003 shows potent activation of 4-1BB and blockade of PD-L1 in cell-based assays. 4-1BB activation was exerted through the bridging of PD-L1 on target cells and 4-1BB on effector cells. No PD-L1-independent activation of 4-1BB was observed. Through X-ray crystallography, a unique binding epitope in the cysteine-rich domain 4 (CRD4) region was resolved that provides high potency and potentially low on-target toxicity as determined by primary immune cell assays and toxicity evaluation in vivo . Conclusions: A unique single-domain antibody was discovered that binds to the CRD4 domain of 4-1BB. When incorporated into a 4-1BB/PD-L1 bispecific (PM1003), we have shown the potent inhibition of PD-L1 activity with 4-1BB agonism upon cross-bridging with PD-L1 in vitro . Antitumor activity with minimal toxicity was found in vivo . Thus, PM1003 is a uniquely differentiating and next generation therapeutic agent for cancer therapy.